NEUROLOGICAL COMPLICATIONS OF INFLUENZA A INFECTION: CASE SERIES OF FIVE PATIENTS IN A TERTIARY PEDIATRIC HOSPITAL - Rsovac, Snezana; Selakovic, Vesna; Kalanj, Jasna; Milosevic, Katarina (Medical Research, 2023)
Introduction: Neurological complications of Influenza infection in a pediatric population vary in incidence and severity. The central nervous system is most often affected in the form of encephalitis and encephalopathy. The most serious complication is acute necrotizing encephalopathy (ANE). The aim of this case study was to present a variety of neuro-influenza in pediatric patients. Methods: We present five children who were hospitalized in the pediatric intensive-care unit due to neurological complications of Influenza-A infection during the winter season of 2022-2023. The identification of the causative agent was carried out by the reverse–transcription–polymerase chain reaction or by the detection of viral antigens in the samples of nasopharyngeal swabs. Results: Four out of five presented patients were male. The average age at admission was 6 years (min. 7 months - max. 11 years). All patients had an acute disturbance of consciousness at admission and four of them had seizures. Neurological complications of Influenza A infection presented as acute encephalitis, posterior reversible encephalopathy syndrome, acute disseminated encephalomyelitis, encephalopathy, and ANE. Neurological signs appeared after a mean of four days of the first symptoms. There was no lethal outcome. Younger patients had more severe brain damage and took longer to recover. None of the children received the flu vaccine. Conclusions: Children presenting with acute neurological deterioration during influenza season should be evaluated for influenza-associated central nervous system complications even if the respiratory involvement is mild or there are no respiratory signs at all. Magnetic resonance imaging is the most important tool for early diagnosis.